Emerging trends of the tumor microenvironment in peritoneal malignancies (2010-2024): a visualization analysis - Duan, Hua; Cheng, Mengqi; Sun, Qianhui; Chen, Cihui (Frontiers in Oncology, 2025)
BackgroundPeritoneal malignancies (PM) represent a group of highly heterogeneous tumors associated with poor prognosis and limited effective treatment options. Recent studies have demonstrated significant progress in understanding the tumor microenvironment (TME) of PM. However, no bibliometric analysis focusing on PM and TME has been conducted. This study aims to provide a comprehensive assessment of the current research landscape and to identify key areas of interest and emerging trends in this field from a bibliometric perspective.MethodsPublications related to the TME in PM from 2010 to 2024 were retrieved from the Web of Science Core Collection database. Microsoft Excel, VOSviewer, CiteSpace, and R package “bibliometrix” were used to perform the visualization analysis.ResultsA total of 862 papers from 56 countries were included. Both annual publication counts and citations have increased steadily over time. The United States of America (USA) contributed the highest number of publications and demonstrated the greatest impact, followed by China and Japan. The University of Texas MD Anderson Cancer Center, Sichuan University and Fudan University were identified as the leading research institutions. Four of the top five most prolific authors are from Japan, including Kajiyama Hiroaki, Yashiro Masakazu, Fushida Sachio and Kinoshita Jun. Cancers published the largest number of articles, with 56 publications, while Cancer research was the most frequently co-cited journal. Reference and keyword burst detection revealed that research hotspots include cytoreductive surgery, hyperthermic intraperitoneal chemotherapy, immunotherapy, tumor-associated macrophages, cancer-associated fibroblast and endothelial growth factor.ConclusionsThis study summarizes recent research frontiers and hotspots regarding the TME in PM and provided valuable references for future investigations. Immunotherapy targeting the TME is likely to become a major research direction.